The Role of Positive Oral Corrective Feedback in Reducing Fossilization among EFL University Students - Bouras, Sana (جامعة حسيبة بن بو علي الشلف - مخبر تعليمية اللغات وتحليل الخطاب, 2018)
يهدف هذا المقال إلى اكتشاف الدور الفعال وراء استعمال التصحيح الشفوي الإيجابي في مساعدة الطلبة لتحسين مستواهم اللغوي الشفوي، حيث أجريت هذه الدراسة مع قسم طلبة السنة الأولى لغة انجليزية بجامعة الشاذلي بن جديد – الطارف – لذلك فإن تقديم التصحيح الشفوي من قبل الأستاذ أثناء تأديتهم للتمارين الشفوية له دور فعال في استعمال مستوى التحجر، كما يرفع وعي الطلبة بطبيعة الأخطاء اللغوية الشفوية مما يؤدي إلى رفع مستواهم في استعمال ونطق الكلمات جيدا، وتوظيفها في السياق اللغوي الشفوي المناسب.
The aim of this study is to investigate whether the employment of positive oral corrective feedback with first year foreign language (EFL) students (LMD) at the University of Chadli Bendjedid El–Tarf plays an effective role in preventing the students’ errors from getting fossilized and correcting their errors if they have already been fossilized. So, positive oral corrective feedback which is provided by the teacher upon students’ errors while performing oral activities reduces errors’ fossilization. Accordingly, students will achieve accuracy and fluency, therefore developing their oral skills.
Keywords: التعليم الجامعي -- تدريس اللغة الإنجليزية -- المهارات الشفوية -- التصحيح الشفوي -- جامعة الشاذلي بن جديد